KEEFEKTIFAN MEDIA WEBSITE LET’S READ UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS 2 SEKOLAH DASAR - Fatimatus Zahro; Nafiah; Rudi Umar Susanto; Suharmono Kasiyun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading Ability Is A Fundamental Skill For Elementary School Children, As It Is The Foundation For Academic Achievement At The Next Level. Students Often Show Poor Reading Skills, Which Negatively Impacts Their Text Comprehension Abilities. This Study Aims To Evaluate The Effectiveness Of The Let's Read Application Or Website In Improving The Reading Skills Of Second-Grade Elementary School Students At An-Nur Islamic Elementary School, Surabaya, And To Describe The Implementation Of Learning By Utilizing The Let's Read Website. Because The Effectiveness Of Let's Read In Improving Reading Skills, Especially In Second-Grade Elementary School An-Nur, Has Not Been Widely Studied Quantitatively. Therefore, This Study Aims To Analyze The Extent To Which The Use Of Let's Read Media Is Effective On Students' Reading Skills And Also Provide New Innovations For An-Nur Islamic Elementary School In Using The Let's Read Website To Improve Students' Reading Skills. This Study Applies A Quasi-Experimental Method With A One Group Pretest–Posttest Design. In This Design, The Study Only Involves One Experimental Group Without A Comparison Group Or Control Group. The Experimental Group Was First Given A Pretest To Determine Students' Reading Abilities Before Receiving Treatment. Next, They Used The Let's Read Website As A Learning Medium, Followed By A Final Assessment (Posttest) To Ensure Improvement In Reading Skills After The Treatment. The Implementation Of Learning Using The Let's Read Website Media Went Very Well And The Results Obtained Were That The Let's Read Website Media Was Effective In Improving The Reading Skills Of Second-Grade Students At Sdi An-Nur Surabaya.